2018
DOI: 10.1007/s11764-018-0692-x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of self-reported cognitive function in cancer patients following chemotherapy treatment

Abstract: This research highlights the need for a standardised approach to measurement of self-reported cognitive symptoms in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
133
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(151 citation statements)
references
References 119 publications
9
133
2
7
Order By: Relevance
“…This was the first review to summarize findings from longitudinal studies on SCI. During data synthesis, a review of SCI (including longitudinal data) was published. As the main purposes of the previous review (ie, the association with SCI) is different, our synthesis provides a unique contribution to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…This was the first review to summarize findings from longitudinal studies on SCI. During data synthesis, a review of SCI (including longitudinal data) was published. As the main purposes of the previous review (ie, the association with SCI) is different, our synthesis provides a unique contribution to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive complaints were reported by ≥50% of breast cancer patients after chemotherapy; however, only 15-25% had objective cognitive decline [57]. Cognitive complaints, often reported by patients with poor emotional status or reported fatigue, are not always linked to objective cognitive disorders [58]. Indeed, many studies showed an association between reported cognitive complaints and psychological factors such as depression [59][60][61] or anxiety [61,62], as well as with fatigue and sleep difficulties [63,64].…”
Section: Long-term Cognitive Disorders In Breast Cancer Survivorsmentioning
confidence: 99%
“…Due to the significant impact on the patient's quality of life (Boykoff, Moieni, & Subramanian, ; Hutchinson, Hosking, & Kichenadasse, ; Lange & Joly, ), a growing body of neuropsychological and neuroimaging studies focuses on cognitive impairment in cancer patients (Joly et al, ). Nevertheless, considering the frequent discrepancies between subjective reports of cognitive difficulties and objective measures from neuropsychological tests (Bray, Dhillon, & Vardy, ; Hutchinson et al, ; Pullens, De Vries, & Roukema, ), overall cancer patients' cognitive complaints do not seem to be good predictors of their objective performances.…”
Section: Introductionmentioning
confidence: 99%